Population-Level Alcohol Consumption and Homicide Rates in Latin America: A Fixed Effects Panel Analysis, 1961–2019 - Escaño, Guillermo Jesús (The British journal of criminology, 2024)
Latin America and the Caribbean (LAC) possesses 8 per cent of the global population but approximately one-third of global homicides. The region also exhibits high per capita alcohol consumption, risky drinking patterns and a heterogeneous mix of beverage preferences. Despite this, LAC violence receives limited attention in the English-language literature and there are no studies of the population-level alcohol-homicide association in the region. We examined the effects on total, male and female homicide rates of total and beverage-specific alcohol consumption (22 nations, 1961-2019) and of risky drinking patterns (20 nations, 2005 and 2010). We collected homicide and alcohol data from the World Health Organization. Panel fixed effects models showed (1) per capita total and wine consumption were positively associated with total, male and female homicide rates, though effects were much stronger for males, (2) per capita beer consumption was positively associated with total and male homicide rates, (3) per capita spirits consumption was not associated with homicide rates, and (4) nations with riskier drinking patterns had higher total, male and female homicide rates than those with less risky drinking patterns.